Journey to textbook affordability: An investigation of students’ use of eTextbooks at multiple campuses - Eun-Ok Baek (Athabasca University Press, 2013)
eTextbooks have steadily and recently more rapidly penetrated the textbook market. In order to effectively support students’ learning, it is important to comprehend students’ experiences using eTextbooks. This survey study was designed to gain an understanding of students’ experiences in using eTextbooks and variables that impact their experiences, perceptions, and attitudes towards eTextbooks. In a total of 33 courses, faculty members at five state university campuses in California participated in the eTextbook pilot project during the fall of 2010. Six hundred and sixty-two student questionnaires were returned from those courses. Key findings include: 1) More than one-third of the students were satisfied with the eTextbook; 2) more than half of the students felt that the eTextbook was easy-to-use; 3) older students (22 or older) tended to have more positive experiences with the eTextbook than younger students; and 4) students most liked the eTextbook’s cost, accessibility, light weight, and keyword search features. This study implies that the eTextbook must be a high-quality, easy-to-use resource to serve as a viable textbook option for student learning.